Chemical composition and antibacterial activity of Origanum ramonense essential oil on the β-lactamase and extended- spectrum β-lactamase urinary tract isolates - Qaralleh, Haitham N. (Bangladesh Journal of Pharmacology, 2018)
The aim of this study was to evaluate the antibacterial activity of Origanum ramonense essential oil extracted from the air-dried leaves against β-lactamase and extended-spectrum β-lactamase obtained from the patients with urinary tract infection. The essential oil was extracted by hydrodistillation and analyzed by GC–MS. In vitro antibacterial activity was studied using disc diffusion and microdilution methods. Twenty compounds were identified representing 97.8% of the total oil. The major components were carvacrol (84.6%), p-cymene (4.3%) and γ-terpinene (3.3%). The oil showed a broad spectrum of antibacterial activity against all tested isolates. Staphylococcus aureus, S. epidermidis, Klebsiella pneumoniae and Enterobacter aerogenes had the lowest minimum inhibitory concentration values (0.015 µg/mL) followed by Escherichia coli (0.14 µg/mL). The lowest susceptible strains to oil were Pseudomonas aeruginosa, Proteus mirabilis, E. coli 25922 and P. aeruginosa 10145. The bacteriostatic and bactericidal effects at concentrations as low as 0.015 µg/mL indicated the potent antibacterial activity of O. ramonense. Video Clip of Methodology: Disc Diffusion method: 2 min 16 sec Click to watch